A aliança empresarial-militar e a ditadura brasileira: a atuação de empresários em escolas militares e de integrantes das forças armadas em companhias privadas durante o regime pós-1964 - Campos, Pedro; Beserra de Vasconcelos, Claudio (Brasiliana: Journal for Brazilian Studies, 2022)
The article analyzes the rapprochement between the military and businessmen and their role in defining the Brazilian dictatorship inaugurated with the 1964 coup. For this, we approach two specific movements. Firstly, we deal with the presence of Brazilian businessmen in schools and military institutions before and during the dictatorship. Then, we problematize the employment of military personnel in private companies throughout the regime. We defend that this form of approximation played a fundamental role in the regime, considering that it expresses the social content and maximum meaning of the dictatorship, which, in our view, presents itself as a business-military regime. To endorse our hypothesis, we used documents from the business community and military archives, which prove this alliance, the basis of the regime implemented in the country since 1964.